Sequence Stratigraphy of South Central Coastal Quaternary Sandy Formation and Stratigraphic Significance - Van Tuan, Nguyen; Nghi, Tran; Van, Tran Tan (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 2, 2019)
Abstract: The South Central Coastal Quaternary sandy formation has been studied by many authors according to different objectives, mainly for establishing quaternary geological maps ata different scale. There are 5 sedimentary cycles established based on the absolute age of the sand, that was analyzed by the method of thermoluminescent dating of quartz (TL), and by the comparison between 5 global glacial /interglacialcycles and 5 sedimentary cycles of the Red River Delta. The Southern Central coastal sandy cycle corresponds to 5 sequences. Sequence 1 has the age of early Pleistocene (Q 1 1 ); Sequence 2 has middle Pleistocene age, early part (Q 1 2a );  Sequence 3 has Pleistocene age in the middle of the late part (Q 1 2b ); Sequence 4 has age of early Late Pleistocene part (Q 1 3a ) and Sequence 5 has age of late Pleistocene - Holocene (Q 1 3b -Q 2 ). Each sequence has 3 systems which tract corresponding to 3 lithofacies complex: (1) Lowstand systems tractcorresponding to alluvial gravelly sand facies complex (arLST) or marine-wind red sand facies complex (mvLST); (2) Transgressive systems tract corresponding to the white sand and spotted white sandy barrier bar facies complex (mtTST); Highstand systems tract corresponding to the marine-wind red sand facies complex (mvHST). Keywords: Sequence startigraphy, sedimentary cycle, systems tract, lithofacies complex. References : [1] Nguyễn Đức Tâm, Đỗ Tuyết, Thuyết minh bản đồ địa chất Đệ Tứ Việt Nam tỷ lệ 1/500000, Viện Khoa học Địa chất và Khoáng sản Việt Nam, 1994. [2] Ngô Quang Toàn (Chủ biên), Vỏ phong hóa và trầm tích Đệ tứ Việt Nam, Cục Địa chất và Khoáng sản Việt Nam, Hà Nội, 2001. [3] Nguyễn Văn Cường (chủ biên), Báo cáo thuyết minh đo vẽ địa chất và tìm kiếm khoáng sản nhóm tờ Hàm Tân-Côn Đảo tỷ lệ 1/50.000, Tổng cục Địa chất và Khoáng sản Việt Nam, 2001. [4] Hoàng Phương (chủ biên), Báo cáo kết quả đo vẽ bản đồ địa chất và tìm kiếm khoáng sản nhóm tờ Phan Thiết tỷ lệ 1/50.000, Tổng cục Địa chất và Khoáng sản Việt Nam, 1997. [5] Lê Đức An, Đinh Ngọc Lựu, Những phát hiện mới về tectit và ý nghĩa của chúng trong việc nghiên cứu địa chất-địa mạo lãnh thổ phía nam Việt Nam, Tập san Bản đồ địa chất 36 (1978) 37- 40. [6] V.Mu. Colin, G.J. Brian, T. Nghi, M.P. David, V.V. Vinh, T.N. Tinh, C.N. Gerald, Thermoluminescene ages for a reworked coastal barier, southeastern Vietnam: preminary report, Journal of Asian Earth Sciences 20 (2002) 535-548. [7] Trần Nghi, Nguyễn Địch Dỹ, Đinh Văn Thuận, Vũ Văn Vĩnh, Ma Công Cọ, Trịnh Nguyên Tính, Môi trường và cơ chế thành tạo cát đỏ Phan Thiết, Tạp Chí Địa chất A/245 (1998) 10-12. [8] Trần Nghi, Địa chất trầm tích Việt Nam, NXB Đại học Quốc gia Hà Nội, Hà Nội, 2018. [9] Trần Nghi, Tiến hóa các thành tạo cát ven biển Miền Trung trong mối tương tác với sự thay đổi mực nước biển trong Đệ Tứ, Tuyển tập các công trình nghiên cứu Địa chất và Địa vật lí biển 2 (1996) 130-138.